2006
DOI: 10.3402/mehd.v18i3-4.7681
|View full text |Cite
|
Sign up to set email alerts
|

Newly identified vitamin K-producing bacteria isolated from the neonatal faecal flora

Abstract: Fat-soluble vitamin K is an essential component of the blood clotting process. Menaquinones are the naturally occurring form of vitamin K identified in bacteria. Lipid extracts were made from three bacteria originally isolated from the human neonatal gut and identified as Enterobacter agglomerans, Serratia marcescens and Enterococcus faecium . Following preparative thin layer chromatography (TLC), the lipid extracts were subjected to liquid chromatography-mass spectrometry (LC-MS) analysis. Peak analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…Besides SCFA, gut microbiota-synthesized micronutrients such as vitamins exhibit beneficial value for both microbial and host metabolisms. Vitamin-K-producing gut bacteria namely Bacteroides fragilis, Eubacterium lentum, Enterobacter agglomerans, Serratia marcescens , and Enterococcus faecium ( Fernandez and Collins, 1987 ; Cooke et al, 2006 ) anaerobically synthesize vitamin K2 (menaquinone) which is essential in decreasing vascular calcification, elevating HDL and lowering cholesterol levels, contributing to lower risk of cardiovascular disorders such as atherosclerosis and coronary heart disease ( Kawashima et al, 1997 ; Geleijnse et al, 2004 ). Gut microbiota also serves as an important source of vitamins B for the host ( Salminen et al, 1998 ; Degnan et al, 2014 ).…”
Section: The Gut Microbiome and Its Multifarious Functionsmentioning
confidence: 99%
“…Besides SCFA, gut microbiota-synthesized micronutrients such as vitamins exhibit beneficial value for both microbial and host metabolisms. Vitamin-K-producing gut bacteria namely Bacteroides fragilis, Eubacterium lentum, Enterobacter agglomerans, Serratia marcescens , and Enterococcus faecium ( Fernandez and Collins, 1987 ; Cooke et al, 2006 ) anaerobically synthesize vitamin K2 (menaquinone) which is essential in decreasing vascular calcification, elevating HDL and lowering cholesterol levels, contributing to lower risk of cardiovascular disorders such as atherosclerosis and coronary heart disease ( Kawashima et al, 1997 ; Geleijnse et al, 2004 ). Gut microbiota also serves as an important source of vitamins B for the host ( Salminen et al, 1998 ; Degnan et al, 2014 ).…”
Section: The Gut Microbiome and Its Multifarious Functionsmentioning
confidence: 99%
“…In white shrimp Litopenaeus vannamei and Fenneropenaeus indicus vast strains of Bacillus have been tested as probiotics in order to improve dry matter digestibility, phosphorus, and crude protein. Consequences of Bacillus administration with a dose of 50 g kg −1 feed revealed higher growth sizes [96] . Other research has suggested the importance of managing the probiotic in all ontogenetic stages of the shrimp to generate a constant effect on the production of digestive enzymes [97] .…”
Section: Digestion Enhancementmentioning
confidence: 96%
“…Vitamin products are among the valuable output of the probiotics. In vitro studies and humans trials have archived the capacity of some selected probiotic strains to compose Vitamin k [96] , folic Acid [97] and B12 [122] . LeBlanc et al [123] stated that certain lactic acid bacteria (LAB) have the privilege of synthesizing water-soluble vitamins such as the B-group (e.g.…”
Section: Vitamin Productionmentioning
confidence: 99%
“…Other gut bacteria have been previously identified as menaquinones producers of various chain lengths, such as Bacteroides ovatus, Enterococcus faecalis, Escherichia coli, Prevotellabuccae,Staphylococcus epidermidis, and Staphylococcus haemolyticus. Some strains isolated from feces of exclusively formula-fed infants were reported as vitamin K producers, e.g., Bacteroides spp., Citrobacter freundii, Enterobacter agglomerans, Enterococcus faecium, Serratia marcescens, Staphylococcus capitis, and Staphylococcus warneri, these bacterial strains are predominantly facultative anaerobes associated with the young neonatal gut where the environment is more anaerobic [82].…”
Section: Effect Of Vitamin K-producing Bacteriamentioning
confidence: 99%